Modernisasi Pesantren Salaf Terhadap Transisi Kehidupan Sosial Dalam Tinjauan Filsafat Sosial - Nurmahmudah, Nurmahmudah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Salaf pesantren is one of the Islamic educational institutions that has a great influence and contribution to Indonesia in encouraging the progress of science and character education. So it is appropriate to study the renewal carried out by these salaf pesantrens. The renewal carried out by these salaf pesantren is a form of answering the needs of a dynamic society. So the review conducted in this paper is to look at the innovation of Hidayatut Thullab pesantren in the review of social philosophy, so the question in this paper is how the social inetarchy relationship between the characters produced between the community or the pesantren family and the educational innovations it makes to society as a whole. The method used is a combination of literature studies and field studies, using the domain analysis method, componen analysis, taxonomy analysis, and cultural theme analysis, the purpose of this method is to find the construction of social situations clearly. The results of the analysis of this paper are, that this semi-modern salaf pesantren has been able to build its social culture clearly, because it is assisted by a curriculum, adequate Islamic material and the environment of pesantren life based on salaf culture, so that the character of social interaction is clearly illustrated as a family or pesantren community that has a strong Islamic identity, a thick cultural culture and tak'dzim to the kiaiKiyai. However, because the innovation is only limited to the digitalisation of online mass media-based da'wah communication, the impact is only in the field of da'wah, and the social environment is also still limited to the relationship network environment, not yet to a more famous national level, as we know that the world of digital communication still needs something unique so that it goes viral and is widely known and captures more people. While the pesantren's relationship with the surrounding community as a form of social interaction has not been carried out optimally, because it is still confined to the salaf pesantren system with a traditional classical paradigm, thus making the salaf pesantren movement more limited than modern pesantren, such as the lack of cooperation between pesantren as a whole as educational institutions to the government and NGOs in order to obtain integrated activities, adequate facilities, teacher support and so on.